Visualizing genealogy through a family-centric perspective. (January 2017) - Ball, Robert
Genealogy is a way to tell a story. Stories tell us who we are, where we came from, and are a foundation for future behavior. Genealogical visualizations are used to help understand and share the story of the past with others. Modern research for genealogy emphasizes the stories of families and communities. However, most genealogical visualizations are focused on the individual and have a number of limitations including not giving accurate stories of families and timelines. This article presents a temporal family-centric visualization paradigm that focuses on families and communities. It is unique in that it shows all the family relationships of individuals while at the same time putting the people into a correct historical and temporal context. In addition, it shows where temporal information is missing and uses heuristics to place people in approximately the right time frame. The new paradigm allows people to understand their stories of their families and the communities that they came from in order to create a whole story with context and details.